2022
DOI: 10.1177/01640275221113219
|View full text |Cite
|
Sign up to set email alerts
|

How Do Marital Transitions Affect Self-Perceptions of Aging?

Abstract: Objectives We analyzed whether marital status and experiences of marital loss or gain were associated with self-perceptions of aging (SPA), a major psychosocial mechanism of healthy aging. Method We used data from 7028 participants of the Health and Retirement Study. Participants reported their marital status and their positive and negative SPA on two occasions 4 years apart. We ran general linear models to analyze differences in SPA between men and women who remained married, became divorced or widowed, or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…A very recent study from the US revealed that not marital status is associated with PA but marital transitions (Turner et al, 2023). Among adults aged 50 and older, spousal loss is associated with less positive PA, while repartnering is related to less negative perceptions compared to remaining married.…”
Section: Previous Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…A very recent study from the US revealed that not marital status is associated with PA but marital transitions (Turner et al, 2023). Among adults aged 50 and older, spousal loss is associated with less positive PA, while repartnering is related to less negative perceptions compared to remaining married.…”
Section: Previous Researchmentioning
confidence: 99%
“…Research has shown that retirement has a major effect on PA (Bordone et al, 2020;Schafer & Shippee, 2010;Zihan & Post, 2020). Moreover, it can be assumed that the timing of widowhood or repartnering can be crucial for PA, since it is chrononormatively different if individuals are, for example, widowed at age 50 or at age 70 (Turner et al, 2023). Reducing the sample to retirees contributed to ensure that the respondents were in a comparable age-specific phase.…”
Section: Independent Variablesmentioning
confidence: 99%
See 3 more Smart Citations